Convergence in the Southern Cone - Elías, Víctor; Fuentes, Rodrigo (Estudios de Economía, 2016)
The main objective of this paper is to analyze the degree of regional economic convergence in the Southern Cone, using regional data of Argentina and Chile during the 1960-1985 period. This study found a more rapid convergence in the case of Chile than in the case of Argentina (which could be due in part to the much higher degree of openness adopted by Chile during the second part of the period analyzed here). The homogeneization of the series of GDP between both countries using purchasing power parity exchange rate, and the consideration of the behavior of the GDP per unit of labor input instead of the GDP per capita, improves substantially the fit of the Barro and Sala-i-Martin equation, when pooling the data of both countries. The ""exogenous"" variables used in the conditional convergence model increase substantially the estimates of the speed of convergence from 0. 71 percent up to 2 percent.